Environmental impacts of using desalinated water in concrete production in areas affected by freshwater scarcity - Alessandro Arrigoni; Tamar Opher; Sabrina Spatari; Valeria Arosio; Heather L. MacLean; Daman K. Panesar; Giovanni Dotelli (Acta Polytechnica CTU Proceedings, 2022)
Up to 500 litres of water may be consumed at the batching plant per cubic meter of ready mix concrete, if water for washing mixing trucks and equipment is included. Demand for concrete is growing almost everywhere, regardless of local availability of freshwater. The use of freshwater for concrete production exacerbates stress on natural water resources. In water-stressed coastal countries such as Israel, desalinated seawater (DSW) is often used in the production of concrete. However, the environmental impacts of this practice have not yet been assessed. In this study the effect of using DSW on the water and carbon footprints of concrete was investigated using life cycle assessment. Water footprint results highlight the benefits of using DSW rather than freshwater to produce concrete in Israel. In contrast, because desalination is an energy intensive process, using DSW increases the greenhouse gas intensity of concrete. Nevertheless, this increase (0.27 kg CO2e/m3 concrete) is small, if compared to the life cycle greenhouse gas emissions of concrete. Our results show that using untreated seawater in the mix (transported by truck from the coast) in place of DSW, would be beneficial in terms of water and carbon footprints if the batching plant were located less than 13 km from the withdrawal point. However, use of untreated seawater increases steel reinforcement corrosion, resulting in loss of structural integrity of the reinforced concrete composite. Sustainability of replacing steel with non-corrosive materials should be explored as a way to reduce both water and carbon footprints of concrete.